Cyclic microwave-assisted synthesis and characterization of nano-crystalline alkaline earth metal tungstates - Phuruangrat A. (2014)
Nano-crystalline MWO4 (M = Ca, Sr and Ba) were successfully produced using cyclic microwave radiation in propylene glycol. XRD, TEM, SAED and EDX analyses revealed the presence of nano-crystalline MWO4 containing the corresponding alkaline earth metals, W and O. Their lattice parameters and crystallite sizes were determined, and enlarged with the increase in the ionic radii of the corresponding divalent metals. Six different vibrations were detected using Raman spectroscopy and very strong W-O stretching of [WO4]2- tetrahedrons using FTIR. ©2008 The Ceramic Society of Japan. All rights reserved.